"الضرورة الشرعية وأثرها في المعاملات المعاصرة -بيع الأعضاء والدم (أنموذجاً)- " - دوغه, ياسين; عبابة, دويم (University of Eloued جامعة الوادي, 2020)
"هذه الدراسة التي عنوانها: الضرورة الشرعية وأثرها في المعاملات المعاصرة –بيع الأعضاء والدم أنموذجا- كانت إشكاليتها التي تسعى للإجابة عليها هي: ما هو أثر الضرورة في المعاملات المعاصرة؟ أجابت الدراسة على ذلك من خلال المباحث التالية: المبحث الأول: خصصته للضَّرورة الشَّرعية, والمبحث الثاني جعلته لأثر الضَّرورة الشَّرعية في بيع الأعضاء, والمبحث الثالث سلطت الضوء على أثر الضرورة في بيع الدم. وتوصلت الدراسة إلى جملة من النتائج, لعل أهمها هو أن العلماء قد أعملوا الضرورة في أحكام المعاملات المعاصرة, وذكرنا بيع الأعضاء والدم نموذجا, كما أوصت الدراسة بضرورة الاهتمام بفقه الضرورة على المستوى العلمي من مختصين وباحثين وطلبة علم, والتعمق في دراستها نظريا وتطبيقيا وإبراز الجانب المقاصدي لهاThis study, which is entitled: The legal necessity and its impact on contemporary transactions - selling organs and blood as an example - its problem that it seeks to answer is : What is the effect of necessity on contemporary transactions? The study answered that through the following researches: The first topic: dedicates it to legal necessity. And the second topic treats the effect of legal necessity in selling organs. And the third topic sheds light on the necessity of selling blood. The study reached a set of results, perhaps the most important of which is that scholars have permitted necessity in contemporary transactions, and we mentioned the sale of organs and blood as an example and the study also recommended the need to pay attention to the jurisprudence of necessity at the scientific level from specialists, researchers and students, and to go deeper in its study, in theory and practice, highlighting its intended goal.
مذكرة ماستر تخصص معاملات مالية معاصرة
Keywords: الضرورة الشرعية - المعاملات المعاصرة - بيع الأعضاء – بيع الدم; Sharia necessity - contemporary transactions - selling organs - selling blood